A Study of Factors Affecting Health Student Behavior on Stunting Issues in East Nusa Tenggara Province, Indonesia - Frans Salesman, Emanuel Gerald Alan Rahmat, Abdul Madjid (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Background: East Nusa Tenggara Province is one of the areas with the highest prevalence of stunting in Indonesia. Programs to prevent and deal with stunting problems are not only through government program interventions but require the role of students as future health worker candidates and nourish an educational function to the community. Objective: This study aims to determine the factors related to the involvement of health students in supporting the prevention of stunting problems in the province of East Nusa Tenggara, Indonesia Method: A cross-sectional study was conducted in this study. The study population was health students at Citra Bangsa University in East Nusa Tenggara, Indonesia. There were 311 respondents in the study. Proportional random sampling is used for sampling. The SPSS 25 program was used to perform descriptive and bivariate data analysis. Result: The results of Spearman's correlation analysis showed that there was a relationship between knowledge variables (p = 0.000; r = 0.389), attitude ((p = 0.002; r = 0.203), and motivation (p = 0.000; r = 0.211) with the intervention of health students in stunting handling programs. Based on the results of the study, it shows that the knowledge variable (r = 0.389), was most related to student involvement in supporting stunting handling programs. Conclusion: The learning process of health students needs to optimize empowerment in aspects of knowledge, attitudes and motivation in teaching, research, and community service activities as factors related to shaping student concern for stunting problems.